The market for onions or lemons? Import substitution and consumer preferences in Senegal - Feyaerts, Hendrik; Maertens, Miet (International Association of Agricultural Economists, 2021)
In Sub-Saharan Africa (SSA), dietary shifts and increasing preference for food quality are thought to be important drivers of food value chain transformation. Yet, in SSA consumer preferences for food quality have not received sufficient attention in the literature, in particular the relation between intrinsic food quality and origin attributes. In this study, we focus on urban consumers in Senegal and their preferences for food quality attributes of local versus imported onion. We conducted a discrete choice experiment with 300 respondents and used conditional logit, regular latent class, scale-adjusted latent class, and attribute non-attendance models to analyze our data. Results indicate that consumers have a high preference for shelf life and firmness, while also ‘localness’ is valued. However, consumers value intrinsic quality attributes differently, depending on the origin label. Consumers have a higher preference for quality when choosing import, while they have a lower preference for quality when choosing for local production. Heterogeneity in preferences for intrinsic onion quality is linked to socio-economic status (income and wealth), residence, access to refrigeration, access to information, and differences in quality perceptions towards local versus imported onions.